Peran Sub Bagian Partisipasi dan Hubungan Masyarakat (Humas) Komisi Pemilihan Umum Provinsi Jawa Timur Dalam Membentuk Citra - Suraiyah, Himmatus; Nur Romdlon Maslahul Adi (Universitas Islam Balitar, 2024)
The Subdivision of Participation and Public Relations (PR) of the General Election Commission (KPU) of East Java Province (Jatim) has an important role in every institution because it is one of the roles in shaping a positive image for each institution. In shaping the image of an institution, public relations has a strong relationship with the media. The research aims to find out how the role of public relations of the East Java KPU in shaping the image of the East Java KPU. This type of research uses descriptive research with a qualitative approach. The results of this study indicate that the division of the Participation and Public Relations Subdivision of the East Java KPU is by utilizing social media and the East Java KPU Website. In the social media of East Java KPU, there are several contents to provide information such as news photos, infographics, comics, public service advertisements. In addition to social media content, the East Java KPU has content on the Website such as news of activities that can be accessed by the public